2019
DOI: 10.1038/s41598-019-52609-4
|View full text |Cite
|
Sign up to set email alerts
|

Kunitz type protease inhibitor from the canine tapeworm as a potential therapeutic for melanoma

Abstract: Modulating the tumor microenvironment to promote an effective immune response is critical in managing any type of tumor. Melanoma is an aggressive skin cancer and the incidence rate is increasing worldwide. Potent protease inhibitors have recently been extensively researched as potential therapeutic agents against various cancers. EgKI-1 is a potent Kunitz type protease inhibitor identified from the canine tapeworm Echinococcus granulosus that has shown anti-cancer activities in vivo. In this study we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Indeed, S. haematobium is a Group-1 carcinogen and, alarmingly, is the leading cause of bladder cancer globally ( 124 ). On the other hand, there is growing evidence showing that parasite infection or parasite-derived products can also reduce cancer tumorigenesis through the induction of apoptosis, activation of the immune response, avoidance of metastasis and angiogenesis ( 125 , 126 ). For the first time, S. mansoni was reported recently to have a therapeutic effect on murine colon cancer ( 57 ).…”
Section: Therapeutic Potential Of Live Schistosome Infection and Schimentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, S. haematobium is a Group-1 carcinogen and, alarmingly, is the leading cause of bladder cancer globally ( 124 ). On the other hand, there is growing evidence showing that parasite infection or parasite-derived products can also reduce cancer tumorigenesis through the induction of apoptosis, activation of the immune response, avoidance of metastasis and angiogenesis ( 125 , 126 ). For the first time, S. mansoni was reported recently to have a therapeutic effect on murine colon cancer ( 57 ).…”
Section: Therapeutic Potential Of Live Schistosome Infection and Schimentioning
confidence: 99%
“…In-depth transcriptomic and proteomic analysis of the different schistosome species and/or different developmental stages, such as egg secretome studies which have led to the discovery of highly sensitive antigens for the diagnosis of schistosomiasis ( 131 135 ) may facilitate the identification of additional molecules with therapeutic potential. An increasing number of candidates applicable for therapy purpose have been identified from other helminths ( 136 ), specific examples being anti-inflammatory protein-2 (AIP-2) from hookworm ( 137 ) and EgKI-1, a potent Kunitz type protease inhibitor from Echinococcus granulosus ( 126 ); on this basis, one could speculate that the schistosome orthologs of these molecules would likely elicit similar therapeutic effects. In addition, if these and other orthologs can provide the requisite therapeutic efficacy, in-depth analysis of the underlying molecular regulatory mechanisms would follow.…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%
“…However, some parasites may also act as negative regulators of cancer. This includes the activation of NK cells and CD8 + T cells seen during Toxoplasma gondii infection and the pro-apoptotic effects of Trypanosoma cruzi infection as well as the Kunitz type protease inhibitor from Echinococcus granulosus , which was shown to induce tumor cell apoptosis in a mouse melanoma model ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that the potassium ion channel blockade function of Kunitz domain-containing peptides grants them the potential application as neuroprotective drugs [ 59 ]. In addition, Kunitz domain-containing proteins also show therapeutic potential in the treatment of cancer [ 60 ] and hereditary angioedema [ 61 ], attributed to their protease inhibition ability.…”
Section: Discussionmentioning
confidence: 99%